Development of an adobe animate-based virtual laboratory for electronic fuel injection practicum - Ghaus Dhiyaurrahman Baunan; Zelhendri Zen; Darmansyah Darmansyah; Rayendra Rayendra (Journal of Educational and Learning Studies, 2026)
This study developed an Adobe Animate–based virtual laboratory for motorcycle electronic fuel injection practicum in vocational high schools. The study applied the Four-D development model involving define, design, develop, and limited disseminate stages. Data were collected through expert validation sheets, practicality questionnaires, pre-test and post-test, and a motivation questionnaire. Data were analyzed using descriptive percentages, N-gain, and paired-samples t-test. The product was highly valid (89.00%) and highly practical (88.06%). Learning outcomes increased from 61.89 to 89.29, with high N-gain (0.72), improved mastery from 21.4% to 92.9%, and significant test results (t = 8.840; p < .001). Student motivation reached a high category (79.11%). The virtual laboratory is feasible and effective for supporting EFI practicum.